Optimization of hot-water extraction of dried yacon herbal tea leaves: Enhanced antioxidant activities and total phenolic content by response surface methodology - Ueda, Yuto; Apiphuwasukcharoen, Nippitch; Tsutsumi, Shuhei; Matsuda, Yasushi; Areekul, Varipat; Yasuda, Shin (My University, 2019)
Yacon (Smallanthus sonchifolius) is an herbal plant and its root has been historically consumed as a sweet vegetable in the Andes. With the research goal of establishing yacon leaves, grown in Japan, as a foodstuff with health benefits, we previously reported the antioxidant effects of yacon tea leaves using concentrated extracts. In this study, we determined the optimum conditions for regular hot-water extraction of yacon tea leaves, intended for normal consumption, aiming for higher activity in several antioxidant assays and total phenolic content (TPC). Response surface methodology was used to optimize the extraction by central composite design. Extraction temperature (ranging from 75.0 to 96.0 ℃) and time (from 2.00 to 5.50 min) were set as the two independent variables. Based on a composite desirability value of 0.863, the hot-water extraction of yacon tea at 89.3 ℃ for 2.50 min was found to be the optimized condition providing higher antioxidant activity and TPC.
Keywords: Antioxidant; Central composite design; Optimization; Response surface methodology; Yacon tea leaves